Molecular Recognition and Quantification of MLH1, MSH2, MSH6, PMS2, and KRAS in Biological Samples. (1st September 2022) - Stefan-van Staden, Raluca-Ioana; Ilie-Mihai, Ruxandra-Maria; Coros, Maria; Pruneanu, Stela
Abstract : Two stochastic sensors based on modification of nitrogen and boron dopped exfoliated graphene with a complex of protoporphyrin and cobalt, were used for molecular recognition and quantification of MLH1, MSH2, MSH6, PMS2 and KRAS biomarkers in biological samples (whole blood, urine, saliva, tumoral tissue). Limits of determination of fg ml −1 magnitude order and broad linear concentration ranges favorized their determination from very low to higher concentrations in biological samples. The student t-test showed that there is no significant difference between the results obtained by utilizing the two microsensors for screening tests, at 99% confidence level, the results obtained being lowr than the tabulated value.